Decision Support System For Selecting Rental Houses Using The Simple Additive Weighting Method (Case Study: Bojong Indah Village) - Sri Rama Putri; Alfi Maulana (SEAN Institute, 2024)
The The development of housing is currently growing quite rapidly, one of which is rented houses, the increasing population growth in Bojong Indah Village has caused the need for housing to continue to increase. Families in Bojong Indah Village are not only native residents, but there are also newcomers. Newcomers and local families need a place to live, such as housing, apartments, and rented houses. However, limited costs are often one of the reasons for not buying a house or apartment. So that rented houses become an alternative choice for the community. In selecting this rented house, the author determines his own criteria in selecting it, namely price, space, distance to the market, security, and parking space. The use of the Simple Additive Weighting (SAW) method in a decision support system is a problem-solving path that can handle this problem, where tenants will feel relieved by the existence of this decision support system by providing suggestions for rented houses that match the criteria quickly by inputting the criteria desired by the user. So that at the end of the process, the user will get a list of recommendations for recommended rented houses based on their input criteria.